Causal associations of gut microbiota and pulmonary tuberculosis: a two-sample Mendelian randomization study - Lu, Zhongkui; Xu, Weiping; Guo, Yidi; He, Fang; Zhang, Guoying (Frontiers in Microbiology, 2024)
The prevalence of pulmonary tuberculosis (PTB) as an infectious disease continues to contribute significantly to global mortality.According to recent studies, the gut microbiota of PTB patients and healthy controls (HCs) show significant disparities. However, the causal relationship between them has yet to be elucidated.We conducted a study using Mendelian Randomization (MR) to explore the potential causal link between gut microbiota and pulmonary tuberculosis (PTB). The summary statistics of the gut microbiota were acquired from the MiBioGen consortium, while data on PTB were sourced from pheweb.jp. A range of statistical methodologies were employed to evaluate causality, encompassing inverse variance weighting (IVW), MR-Egger, weighted median (WM), weighted model, and simple model. We utilized instrumental variables (IVs) that have a direct causal relationship with PTB to annotate SNPs, aiming to discover the genes harboring these genetic variants and uncover potential associations between host genes and the microbiome in patients with PTB.Results: Among the 196 bacterial traits in the gut microbiome, we have identified a total of three microbiomes that exhibit a significant association with PTB. The occurrence of Dorea (P=0.0458, FDR-adjusted P=0.0458) and Parasutterella (P=0.0056, FDR-adjusted P=0.0168) was linked to an elevated risk of PTB, while the presence of Lachnoclostridium (P=0.0347, FDR-adjusted P=0.0520) demonstrated a protective effect against PTB. Our reverse Two-Sample Mendelian Randomization (TSMR) analysis did not yield any evidence supporting the hypothesis of reverse causality from PTB to alterations in the intestinal flora.We have established a connection between the gut microbiota and PTB through gene prediction analysis, supporting the use of gut microecological therapy in managing PTB and paving the way for further understanding of how gut microbiota contributes to PTB's development.